Pengembangan Ensiklopedia Mini Sejarah Pemikiran Ekonomi Sebagai Penguatan Literasi Digital Mahasiswa Pendidikan Ekonomi - Puri, Lilian Mega; Budiono, Desi; Wibawa, Fajri Arif (LPPM UM Metro, 2026)
This research based on the R&D’s Model of ADDIE which are composed by 5 steps of the development process. There are Analysis, Design, Development, Implementation and Evalluation. This research aims to produce a flipbook-based mini encyclopedia of the history of economic thought to strengthen the digital literacy of economic education’s students. Research instruments include interviews, questionnaires and documentation. The validation test was carried out by one media expert and one material expert. The results of the first phase of media expert validation test obtained a result of 80% with valid criteria, and the results of the second stage validation test after a simple revision obtained a result of 96% with very valid criteria. For the validation test of material experts obtained a percentage of 96% with very valid criteria. The practicality test were carried out on 13 students of economic education class of 2023 and obtained a percentage result of 96%. Therefor, it can be concluded that the product of this research is valid and practical to be used in the field to support the digital literacy of the economic’s education’s students in the univesity.Keywords : Encyclopedia, Development, Digital Literacy